Barriers to Bachelor's Degree Completion among College Students with a Disability. (October 2020) - Carroll, Jamie M.; Pattison, Evangeleen; Muller, Chandra; Sutton, April
One of the fastest growing groups on college campuses is students with disabilities, but their rates of bachelor's degree completion remain low. We build on research about barriers to degree completion among historically underrepresented groups on college campuses to examine the extent to which academic preparation before college and processes during college contribute to gaps in bachelor's degree completion among four-year college students with a mental or physical disability. Using the Beginning Postsecondary Students Longitudinal Study, we find that students with a mental disability are significantly less likely to complete a bachelor's degree than students without disabilities and students with a physical disability, net of students' family and academic background. Decomposition of the estimated indirect effect of mental disability on degree completion reveals first-year academic performance as the largest contributor. We discuss the theoretical and practical implications for understanding the barriers faced by college students with a mental disability.